Assessment of agriculture technologies for use in arid regions of Egypt - Metawi H.R.M. (Technology creation and transfer in small ruminants: roles of research, development services and farmer associations, 2014)
The study was carried out in the coastal zone of Western Desert of Egypt (CZWD), which extends from Alexandria at the East to Libyan border at the West. It is classified as an arid zone. The agro-pastoral production system prevails in this area. This system is facing more frequent droughts whose effects are worsened by human activities. Over the last two decades, goat breeding and nutrition technologies were implemented in this area in order to improve goat productivity and profitability. A survey was conducted with 262 Bedouins, aiming to analyze the potential impact of such alternative technologies, highlighting the socioeconomic factors that affect the adoption of these technologies In Egypt. Bio-economic data were collected and submitted to cost-benefit analysis. Results showed that under drought conditions the high rate of kids mortality (22.2%) is the major constrain limiting productivity. The financial analysis of goat production revealed a break even. Replacement of Barki goats by Damascus crossbred increased profit/doe by LE 64.4. On the other hand, enhance nutritive value of crop byproducts decreased cost/doe by LE 54.4.The average adoption of goat production technology was 48.5%. Bedouins adopted breeding technology (74%) and nutrition technology (23%). Adoption of the technology is significantly affected by Bedouins education level, contact with extension agents and total area of owned land. Infrastructure and support services must be established to enable such technologies to succeed and reach small-scale breeders.
8. Seminar of the FAO-CIHEAM Sub-Network on Production Systems, 2013/06/11-13, Tangier (Morocco)